2021
DOI: 10.3389/fpsyt.2021.713614
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Regional Homogeneity of Medication-Free Major Depressive Disorder Patients With Different Onset Ages

Abstract: Background: Neurobiological mechanisms underlying the development of major depressive disorder (MDD) may differ depending on onset ages. Our aim was to determine whether regional homogeneity (ReHo) changes in early-onset depression (EOD) and late-onset depression (LOD) are different, which could also delineate EOD and LOD.Methods: Ninety-one MDD patients and 115 healthy controls (HCs) were recruited, and resting-state functional magnetic resonance imaging data were collected. The ReHo comparison was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Decreased ReHo values were observed in the left precentral gyrus and were positively correlated with EPQ-N scores and negatively correlated with EPQ-L scores in the patients. Reduced ReHo values of the left precentral gyrus in patients with MDD have been found in the published literature (Zhang et al, 2021;Song et al, 2022). Previous studies have shown that patients with MDD who attempted suicide had fewer hemodynamic responses in the left precentral gyrus than patients with MDD without suicidal ideation and HCs (Tsujii et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…Decreased ReHo values were observed in the left precentral gyrus and were positively correlated with EPQ-N scores and negatively correlated with EPQ-L scores in the patients. Reduced ReHo values of the left precentral gyrus in patients with MDD have been found in the published literature (Zhang et al, 2021;Song et al, 2022). Previous studies have shown that patients with MDD who attempted suicide had fewer hemodynamic responses in the left precentral gyrus than patients with MDD without suicidal ideation and HCs (Tsujii et al, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…In this study, POPP patients also had greater ALFF values in the right triangular inferior frontal gyrus. Previous studies had shown that early onset depression had more abnormal prefrontal ReHo values than late-onset depression, and the neuropathological mechanism of recurrent depressive episode was more complex than that of first depressive episode, but both of them were dominated by abnormalities of the right inferior frontal gyrus (triangular part) [33,34]. This suggested that the right triangular inferior frontal gyrus was involved in the process of depression.…”
Section: Discussionmentioning
confidence: 96%
“…Further, it was also associated with the early-onset depression (EOD) and late -onset depression (LOD). Zhang et al ( 40 ) found the EOD patients exhibited increased activation in the right triangular IFG compared with the LOD patients. They indicated that the specific brain alterations of EOD and LOD patients could be associated with different clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%